DOP79 Primary hypogammaglobulinemia with IBD-like features: An ECCO CONFER Multicenter Case Series. (27th May 2021) - Albshesh, A; Eder, P; Ribaldone, D G; Oldenburg, B; De Boer, N K; Mantzaris, G J; Savarino, E V; Dragoni, G; Weisshof, R; Truyens, M; Festa, S; Maillard, M H; et al.
Abstract: Background: The most commonly recognized clinical feature of hypogammaglobulinemia is recurrent infections with high prevalence of gastrointestinal manifestations. In some cases, clinical and endoscopic features are indistinguishable from those of inflammatory bowel disease (IBD). Methods: This was a multicenter case series performed as a part of the Collaborative Network of Exceptionally Rare case reports (CONFER) project. Results: This report includes 25 patients with primary hypogammaglobinemia and IBD-like features [20 males and 5 females, mean age 50 years (±21.7 SD)]. Crohn's disease-like features were noted in 22 patients, three patients had ulcerative colitis-like features. The diagnosis of hypogammaglobulinemia preceded IBD-like features diagnosis in 20 patients (mean of 7.7 years prior, range 0.3–35 years), and followed IBD-like features appearance in 5 cases (mean of one year after, 0.4- 9.1 years). Hypogammaglobinemia etiologies were common variable immunodeficiency (72%), Agammaglobulinemia (8%), selective IgA-deficiency (8%), Goods syndrome (8%), IgG subclass deficiency with IgA deficiency (4%). In addition to antibiotics and intravenous immunoglobulin (IVIG) as a treatment for hypogammaglobinemia, fifteen patients received IBD treatment during the follow-up period, of whom two were on 5-aminosalicylic acid, five on corticosteroids, three on immunomodulatory, four on anti-tumor necrosis factor, and one on vedolizumab. By the end of the follow-up [35.5 months (Interquartile range 18–75)], 20 of 25 (80%) patients were in clinical remission. Conclusion: This case series illustrates a strong male and CD-like features predilection. The diagnosis of IBD-like features mainly occurs after that of hypogammaglobulinemia, the majority of cases successfully recovered after appropriate treatment.